Implementasi Konsep Final Spending Monzer Kahf dalam Meningkatkan Pendapatan Nasional - Firdaus, Muhammad Irkham; Pradhana, Theo Aditya; Alafianta, Novan Fatchu; Tifani, M. Akhlis Azamuddin; Aziz, Muhammad Abdul (MUSLIM HERITAGE, 2023)
AbstractThe benchmark for improving a country's economy is determined by the amount of national income generated from various sectors. National income is influenced by several factors, namely aggregate demand and supply, investment, consumption, and savings. In order to increase the national income of a country, new instruments are needed in the economic system. The Final spending Monzer Kahf concept offers a new policy that connects factors that affect national income with zakat, infaq, and shadaqah instruments. This study aims to link the concept of Monzer Kahf's final spending with an increase in state income. This type of research is Library Research, where the data sources are taken from books, journal articles, and other documentation. While the method used is a qualitative descriptive method. The results of this study are that the concept of final spending by Monzer Kahf is the final expenditure for a Muslim consumer, spending on needs that are in accordance with maslahah  and the obligation to pay zakat-infaq for mustahik zakat. Because with zakat, public consumption will increase, this is because the muzakki will help the needy and poor in meeting their needs, so that it will affect supply and demand, which will also increase national income in a country. AbstrakTolak ukur peningkatan perekonomian suatu negara ditentukan oleh jumlah pendapatan nasional yang dihasilkan dari berbagai sektor. Pendapatan nasional dipengaruhi oleh beberapa faktor, yaitu permintaan dan penawaran agregate, investasi, konsumsi, dan tabungan. Guna meningkatkan pendapatan nasional sebuah negara, maka diperlukan instrumen baru dalam sistem perekonomian. Konsep Final spending Monzer Kahf menawarkan kebijakan baru yang menghubungkan faktor-faktor yang mempengaruhi pendapatan nasional dengan instrumen zakat, infak, dan shadaqah. Penelitian ini bertujuan untuk menghubungkan kosep final spending Monzer Kahf dengan peningkatan pendapatan negara. Jenis penelitian ini adalah Library Research, dimana sumber data yang diambil dari buku, artikel jurnal, dan dokumentasi yang lainnya. Sedangkan metode yang digunakan adalah metode disktiptif kualitatif. Hasil dari penelitian ini adalah bahwa konsep final spending Monzer Kahf adalah pembelanjaan akhir bagi seorang konsumen Muslim, pembelanjaan kebutuhan yang sesuai dengan maslahah  dan kewajiban membayar zakat-infak bagi para mustahik zakat. Karena dengan adanya zakat, konsumsi masyarakat akan meningkat, hal ini disebabkan oleh para muzakki akan membantu fakir dan miskin dalam memenuhi kebutuhan, sehingga hal tersebut akan mempengaruhi permintaan dan penawaran, yang sekaligus akan menambah pendapatan nasional dalam suatu negara.